Law No. 152 of the year 2020 Promulgating The Law on the Development of Micro Small and Medium-Sized Enterprises = قانون تنمية المشروعات المتوسطة والصغيرة والمتناهية الصغر - Egypt; The middle east library for economic services, translator. (2025)
Part-1: Definitions Part - 2: Facilitating access to finance Chapter - 1: Chapter- 2: 7. Temporary allocation Setting order of priority for satisfaction of finance providers' righ Regulating usufruct over real property allocated for MSMES' purposes Settlement of public treasury's claims by enterprises in distress %3D Chapter - 3: Chapter - 4: 13 Part-3: Incentives Chapter - 1: Chapter - 2: Chapter - 3: 15 Non-tax incentives for MSMEs 15 Tax incentives for MSMEs LI Incentives for Companies and Facilities Supporting 18 Small and Micro Enterprises and Entrepreneurships Cases of ineligibility for incentives Chapter - 4: Part-4: Streamlining procedures of commencement of activity 22 Part - 5: The micro, small pun medium-sized enterprises 30 development agency MSMEDA Part – 6: Regularization of statuses of MSMEs Operating in the 35 Informal Economy Part - 7: Simplified principles for permanent tax treatment Part-8: Miscellaneous provisions Part-9: Penalties